Defense Mechanism of the Main Character of The Invisible Man Film - Rezeki, Maretius Oji; Tawakal, Alamsyah; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This study aimed to find out the types of anxiety and defense mechanisms experienced by the main character, Cecilia, in the film (The Invisible Man). The theory used is the theory of Sigmund Freud such as neurotic anxiety, moral anxiety and realistic anxiety, and defense mechanisms such as repression, sublimation, displacement, rationalization projection, reaction formation, denial, and fantasy. The data in this study were taken from the film The Invisible Man (2020) directed by Leigh Whennel. The results of this study found that the anxiety experienced by Cecilia, namely neurotic anxiety (fear unknown danger) and realistic anxiety (fear in face to face in real condition). Thus, the defense mechanism used in reducing anxiety by Cecilia is repression (represses mind to subconscious) and is followed by several other defense mechanisms, namely rationalization (more acceptable), fantasy (imagination), denial (denied accusations), and reaction formation (over protective). What can be underlined in this study is that in the invisible man film, Cecilia as the main character uses a defense mechanism, to reduce the anxiety she experiences.